Respuestas

  • Usuario de Brainly
2013-09-10T01:59:04+02:00
Solución:
1) (1 - Cos(x) )^2 + ( 1 + Cos(x) )^2 = 2(1 + 2 Cos(x)^2)
entonces:
1 - 2Cos(x) + Cos(x)^2 + 1 + 2Cos(x) + Cos(x)^2
2 + 2 Cos(x)^2
2 ( 1 + Cos(x)^2 ) => Respuesta.

2) -Tg(x)^2 + Sec(x)^2 + Sen(x)^2 + Cos8x)^2 = 2

-Tg(x)^2 + Sec(x)^2 + 1
-(Sen(x)^2 / Cos(x)^2) +  (1 / Cos(x)^2) + 1
{-Sen(x)^2 + 1 + Cos(x)^2} / Cos(x)^2
{Cos(x)^2 - Sen(x)^2 + 1} / Cos(x)^2
{2Cos(x)^2 - 1 + 1} / Cos(x)^2
(2Cos(x)^2 / Cos(x)^2
2 => Respuesta.

Espero haberte ayudado. Suerte